Rat cholangiocytes absorb bile acids at their apical domain via the ileal sodium-dependent bile acid transporter. - Lazaridis, K N (1997)
Although bile acid transport by bile duct epithelial cells, or cholangiocytes, has been postulated, the details of this process remain unclear. Thus, we performed transport studies with [3H]taurocholate in confluent polarized monolayers of normal rat cholangiocytes (NRC). We observed unidirectional (i.e., apical to basolateral) Na+-dependent transcellular transport of [3H]taurocholate. Kinetic studies in purified vesicles derived from the apical domain of NRC disclosed saturable Na+-dependent uptake of [3H]taurocholate, with apparent Km and Vmax values of 209+/-45 microM and 1.23+/-0.14 nmol/mg/10 s, respectively. Reverse transcriptase PCR (RT-PCR) using degenerate primers for both the rat liver Na+-dependent taurocholate-cotransporting polypeptide and rat ileal apical Na+-dependent bile acid transporter, designated Ntcp and ASBT, respectively, revealed a 206-bp product in NRC whose sequence was identical to the ASBT. Northern blot analysis demonstrated that the size of the ASBT transcript was identical in NRC, freshly isolated cholangiocytes, and terminal ileum. In situ RT-PCR on normal rat liver showed that the message for ASBT was present only in cholangiocytes. Immunoblots using a well-characterized antibody for the ASBT demonstrated a 48-kD protein present only in apical membranes. Indirect immunohistochemistry revealed apical localization of ASBT in cholangiocytes in normal rat liver. The data provide direct evidence that conjugated bile acids are taken up at the apical domain of cholangiocytes via the ASBT, and are consistent with the notion that cholangiocyte physiology may be directly influenced by bile acids.